Relationship of Knowledge, Lactation Facilities and Superior Support with Breastfeeding (ASI) for Babies, for Mothers who Work at the Daya Guna PO Factory in the Nawangsasi Health Center Work Area in 2021 - Depiriyani Depiriyani; Satra Yunola; Helni Anggraini (Science Midwifery, 2022)
Background: The World Health Organization (WHO) and UNICEF recommend that mothers, if possible, give exclusive breastfeeding for up to 6 months by applying Early Initiation of Breastfeeding (MDI) for approximately 1 hour immediately after the birth of the baby, exclusive breastfeeding is given to the baby only breast milk without additional food. or drinks, breast milk is given on demand or according to the baby's needs every day for 24 hours. The purpose of this study was to determine knowledge, lactation facilities, support from superiors by giving breast milk to infants for mothers who work in PO factories. effectiveness in the working area of ​​the Nawangsasi Health Center in 2021. This study used an analytical survey method with a cross sectional approach. The population used in this study were all working mothers who had babies aged 7-24 months at the PO. The utilization of the working area of ​​the Nawangsasi Health Center in 2021 is 50 people. The sampling technique in this study was simple random sampling by making the entire population a sample of 33 people. The results of univariate analysis were obtained as many as 10 (33.3%) respondents had good knowledge as many as 11 (30.3%) knowledge was quite good and knowledge was not good as many as 12 (36.4%), as many as 26 ( 78.8%) respondents stated that they had lactation facilities and as many as 7 (21.2%) and as many as 22 (66.7%) respondents had supervisor support and as many as 11 (33.3%) respondents did not have supervisor support. From the results of bivariate analysis of data using the chi-square statistical test showing the limit of significance =0.05, it was found that there was a significant relationship between knowledge and breastfeeding for infants in working mothers with p.value 0.007, there was a significant relationship between lactation facilities. with breastfeeding for infants in working mothers with p.value 0.008 and there is a significant relationship between supervisor support and breastfeeding for infants in working mothers with p-value 0.001. Based on the results of this study, it is expected to be a contribution to advice for factory leaders in an effort to increase breastfeeding for infants for working mothers in the working area of ​​the Nawangsasi Health Center. it was found that there was a significant relationship between knowledge and breastfeeding for infants in working mothers with p.value 0.007, there was a significant relationship between lactation facilities. with breastfeeding for infants in working mothers with p.value 0.008 and there is a significant relationship between supervisor support and breastfeeding for infants in working mothers with p-value 0.001.